FEATURES OF THE IMPLEMENTATION OF ACADEMIC CAREER SUPPORT AND GRADUATES' EMPLOYMENT IN THE USA - Hanna Chornoivan (Borys Grinchenko Kyiv Metropolitan University, 2023)
The article is devoted to the peculiarities of professional development, employment and academic career in the USA. It is emphasized that for the successful development of an academic career, it is necessary to apply a systematic approach, in particular, to take into account personal development, continuous learning and career management. The practice of the American National Association for Career Development is considered, the prerequisites and resources for career growth are determined. Presented are practical tools for self-assessment and diagnosis of career paths, an opportunity for researchers at various career stages to participate in a mentoring program for leadership development, sharing experiences, planning and achieving goals, supporting continuous career growth and lifelong learning. The article analyzes the experience of organizing professional development and of support for career of employees in leading USA universities: Harvard University, Stanford University, and the Massachusetts Institute of Technology. Attention is focused on the joint mission of the institutions, which consists in the value for human capital development through the comprehensive realization of the potential of each individual, the creation of favourable conditions for life and professional growth, decent financial support and career growth prospects. It is noted that the main trends in the development of the academic career and employment of graduates of the mentioned institutions in the USA include internal mobility, professional development, continuous training and professional development, organization and activity of professional networks, career coaching, mentoring program.